Variaciones de la arteria del nodo sinoatrial en población colombiana (2012)
Background. Accurate knowledge regarding the cardiac conduction system’s anatomical-physiological integration is essential for understanding the pathophysiology, diagnosis and management of many complications regarding coronary disease and heart disease in general. One of the more variable fundamental aspects, having the greatest clinical impact, concerns the origin and course of arteries irrigating the sino-atrial node (SAN). Objective. Determining the origin, course and distribution of arteries supplying the SAN in a sample of the Colombian population. Materials and methods. 60 cardiopulmonary and digestive blocks were taken by convenience sampling. Conventional dissection of the genitalia determined gender; the coronary artery was then dissected, specifically the SAN, to establish origin and route. Results. It was found that 75% of the SAN artery’s blood supply came from the right coronary artery (RCA), 15% from the circumflex artery and 10% was co-dominant. 86.6% of courses were linear; 13.4% were Y-shaped or Yand double trident shaped. Conclusions. The prevalence of SAN artery origin in the RCA in this study was consistent with similar research findings, regardless of geographical and racial origin. However, this study report some courses not previously described in the literature, such as Y-, double Y-, inverted K- and trident-shaped forms